E-Government During the Pandemic: Maturity Assessment of the Provincial And Regency/City Website in West Sumatra - Amsal Djunid; Asniati Asniati; Rayna Kartika; Indah Permata Suryani; Ares Albirru Amsal (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
E-government uses information technology to change government relations with citizens, the private sector, and other institutions. The importance of identifying e-government performance cannot be separated from the use of the website. Thus, assessing the website quality is very important as it helps determine the quality of e-government services and improve service processes. In almost two years of implementing e-government in West Sumatra, there has been no evaluation of the provincial and district/city government websites, which are the primary tools for implementing e-government today. In the Covid-19 pandemic period, the website's role has become more critical as a means for the public to get the latest information regarding developments in handling the pandemic. This study focuses on assessing and evaluating the level of maturity (maturity assessment) of the provincial and district/city government websites in implementing e-government and its relationship in response to the Covid-19 pandemic. Forty websites were assessed for their e-government maturity in this study. The website consists of 19 district/city websites, one provincial webpage, and 20 websites for handling Covid-19 for each district/city and province. The maturity assessment was measured using the United Nations (UN) e-government maturity model. This study found that government websites are still at stage 1 and stage 2 maturity models. Meanwhile, the Covid-19 handling website is on stage1. It is hoped that the government in West Sumatra will pay more attention to improving e-government through websites in the current pandemic era.